Structural and dielectric properties of Al-doped ZnO nanostructures - Zamiri, Reza
Pure and 2 mol% Aluminium (Al) doped ZnO nanostructures were prepared by a simple and low cost wet chemical precipitation technique. Structure and morphology of the prepared samples were investigated by X-ray diffraction (XRD) and scanning electron microscopy (SEM). UV-visible spectrometry and band gap calculations confirmed the presence of structural defects in the samples. A significant enhancement in dielectric constant resulted from the incorporation of Al in ZnO lattice while an opposite trend was observed for dielectric lost. In addition, the electrical conductivity of Al-doped ZnO samples increased in comparison with that of pure ZnO due to the increase of available charge carriers after replacement of Zn ions by Al ions. (C) 2013 Elsevier Ltd and Techna Group S.r.l. All rights reserved.